Abdominal aortic and junctional tourniquet versus zone III resuscitative endovascular balloon occlusion of the aorta in a swine junctional hemorrhage model. Issue 2 (February 2020) - Schechtman, David W.; Kauvar, David S.; De Guzman, Rodolfo; Polykratis, I. Amy; Prince, M. Dale; Kheirabadi, Bijan S.; Dubick, Michael A.
Abstract : BACKGROUND: Junctional hemorrhage is a leading contributor to battlefield mortality. The Abdominal Aortic and Junctional Tourniquet (AAJT) and infrarenal (zone III) resuscitative endovascular balloon occlusion of the aorta (REBOA) are emerging strategies for controlling junctional hemorrhage, with AAJT currently available in select forward deployed settings and increasing interest in applying REBOA in the military prehospital environment. This study compared the hemostatic, hemodynamic, and metabolic effects of these devices used for junctional hemorrhage control. METHODS: Shock was induced in anesthetized, mechanically ventilated swine with a controlled hemorrhage (20 mL/kg) and closed femur fracture followed by uncontrolled hemorrhage from a partial femoral artery transection (40% total hemorrhage volume). Residual femoral hemorrhage was recorded during 60-minute AAJT (n = 10) or zone III REBOA (n = 10) deployment, and the arterial injury was repaired subsequently. Animals were resuscitated with 15 mL/kg autologous whole blood and observed for 6 hours. RESULTS: One animal in each group died during observation. Both devices achieved hemostasis with mean residual femoral blood loss in the AAJT and REBOA groups of 0.38 ± 0.59 mL/kg and 0.10 ± 0.07 mL/kg ( p = 0.16), respectively, during the 60-minute intervention. The AAJT and REBOA augmented proximal blood pressure equally with AAJT allowing higher distal pressure than REBOA during intervention ( p < 0.01). Following device deflation, AAJT animals had transiently lower mean arterial blood pressure than REBOA pigs (39 ± 6 vs. 54 ± 11 mm Hg p = 0.01). Both interventions resulted in similar degrees of lactic acidemia which resolved during observation. Similar cardiac and renal effects were observed between AAJT and REBOA. CONCLUSION: The AAJT and REBOA produced similar hemostatic, resuscitative, and metabolic effects in this model of severe shock with junctional hemorrhage. Both interventions may have utility in future military medical operations. Abstract : Supplemental digital content is available in the text.